2013
DOI: 10.1007/s00167-013-2637-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and radiographic outcome of patello-femoral realignment procedures: a minimum of 15-year follow-up

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
2
27
0
5
Order By: Relevance
“…20 Both groups also had similar knee osteoarthritis outcome score, Kujala's score, and pain and incidence of work change. 20 Radiographically, the patellar height and the evaluation of tibiofemoral and patellofemoral osteoarthritis were also similar amongst the two groups. 20 These similarly suggest that the addition of proximal realignment procedures do not significantly alter the outcomes of distal realignment procedures postoperatively.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…20 Both groups also had similar knee osteoarthritis outcome score, Kujala's score, and pain and incidence of work change. 20 Radiographically, the patellar height and the evaluation of tibiofemoral and patellofemoral osteoarthritis were also similar amongst the two groups. 20 These similarly suggest that the addition of proximal realignment procedures do not significantly alter the outcomes of distal realignment procedures postoperatively.…”
Section: Discussionmentioning
confidence: 77%
“…20 When compar-ing between the distal realignment and combined group, Vivod et al found that there was no significant difference with regards to the proportions of postoperative patellofemoral dislocations, centralization of the patella, apprehension test, and increased lateral patellar motion. 20 Both groups also had similar knee osteoarthritis outcome score, Kujala's score, and pain and incidence of work change. 20 Radiographically, the patellar height and the evaluation of tibiofemoral and patellofemoral osteoarthritis were also similar amongst the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations